2021
DOI: 10.1111/jfd.13523
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of heat‐killed and formalin‐killed vaccines against Tilapia tilapinevirus in juvenile Nile tilapia (Oreochromis niloticus)

Abstract: Tilapia tilapinevirus (also known as tilapia lake virus, TiLV) is considered to be a new threat to the global tilapia industry. The objective of this study was to develop simple cell culture-based heat-killed (HKV) and formalin-killed (FKV) vaccines for the prevention of disease caused by TiLV. The fish were immunized with 100 µl of either HKV or FKV by intraperitoneal injection with each vaccine containing 1.8 × 10 6 TCID 50-inactivated virus. A booster vaccination was carried out at 21-day postvaccination (d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…In our previous study, vaccination of tilapia juveniles with HKV and FKV resulted in a significant increase in systemic TiLV-specific IgM and high level of protection against TiLV challenge (RPS = 71.3% to 79.6%) [20]. However, persistence of specific antibody was not evaluated.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In our previous study, vaccination of tilapia juveniles with HKV and FKV resulted in a significant increase in systemic TiLV-specific IgM and high level of protection against TiLV challenge (RPS = 71.3% to 79.6%) [20]. However, persistence of specific antibody was not evaluated.…”
Section: Discussionmentioning
confidence: 93%
“…Most recently, water-based inactivated vaccines prepared with heatkilled or formalin-killed TiLV were shown to provide good levels of protection in juvenile tilapia, with RPS of 71.3% and 79.6%, respectively [20]. It has also been reported that TiLV vaccines can induce both humoral immunity and cell mediated immunity [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The TiLV inactivated vaccines were prepared as described previously by Mai et al (2021). Briefly, TiLV strain TH-2018-K, which was isolated from Nile tilapia during a TiLV outbreak in Thailand in 2018 [20], was propagated on E11 cells, in Leibovitz's L15 medium (Sigma, Saint Louis, MO, USA) containing 5% fetal bovine serum, until a cytopathic effect (CPE) of approximately 80% of the cell monolayer was achieved.…”
Section: Vaccine Preparationmentioning
confidence: 99%
“…The TiLV inactivated vaccines were prepared as described previously by Mai et al (2021). Briefly, TiLV strain TH-2018-K, which was isolated from Nile tilapia during a TiLV outbreak in Thailand in 2018 [20], was propagated on E11 cells, in Leibovitz's L15 medium (Sigma, Saint Louis, MO, USA) containing 5% fetal bovine serum, until a cytopathic effect (CPE) of approximately 80% of the cell monolayer was achieved. The supernatant containing the virus was collected and clarified to remove cell debris, by centrifuging at 4500× g for 5 min at 4 • C. Virus concentration was determined using 50% tissue culture infectious dose (TCID 50 /mL) [30].…”
Section: Vaccine Preparationmentioning
confidence: 99%
See 1 more Smart Citation